Komunikasi Perempuan Bercadar: Studi Fenomenologi - Musrifah Musrifah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
An objective view the reconstructed media creates stereotypes veiled women with a negative stigma as the wife of a terrorist, exclusive, bigoted and even hypocritical. This study aims to describe verbal and nonverbal communication veiled women. Good communications made with other veiled women, with their family (husband and children) as well as with the general public. This study utilized qualitative method with phenomenological perspective. In the tradition of phenomenology, data were collected both by observation (nonparticipant) and in-depth interviews (depth interview). This study is a field research study. The research was conducted in several communities of veiled women. They are veiled women communities in Sedayulawas Village (Brondrong sub-district, Lamongan), Blimbing village (Paciran sub-district, Lamongan), Tenggulun village (Solokuro sub-district, Lamongan), and Srowo village (Sidayu sub-district, Gresik). Result of this study shows that veiled women used some Arabic terms while communicating in their own community. They also bear certain labeling which embedded by the people around them. This becomes a part of their verbal communication which they establish with their own community. Whilst, their nonverbal communication shown in form of body language, physical appearance, paralanguage, colors, spatial orientation, personal distance and artifacts.